Influence of short-term chronic oral cannabidiol application on muscle recovery and performance after an intensive training protocol - a randomized double-blind crossover study - Eduard Isenmann; Sebastian Veit; Ulrich Flenker; Alessio Lesch; Dirk W. Lachenmeier; Patrick Diel (Taylor & Francis Group, 2024)
ABSTRACTBackground Rapid regeneration after intense exercise is essential for competitive athletes. Based on this assumption, supplementation strategies, focusing on food supplements, are increasing to improve the recovery processes. One such supplement is cannabidiol (CBD) which is gaining more attention in competitive sports. However, the evidence is still lacking and there are no data available about the effect of a short-term chronic application.Methods A three-arm double-blind cross-over study was conducted to determine the effects of two different CBD products on performance, muscle damage and inflammatory processes in well-trained athletes. In total 17 subjects took successfully part in this study. Each subject underwent the six-day, high-intensity training protocol three times. After each training session, each subject took either a placebo or a CBD product (60 mg of oil or solubilisate). Between the intervention phases, at least four weeks of washout period was conducted. Before and after the training protocols the performance capacity in countermovement jump (CMJ), back squat (BS), bench press (BP) and 1-mile run were measured and biomarkers for muscle damage (creatine kinase, myoglobin), inflammatory processes (interleukin 6 and 10) and immune cell activity (ratios of neutrophil granulocytes, lymphocytes and, platelets) were analyzed. For statistical analyses, the current version of R and a linear mixed model was used.Results It could identify different effects of the training protocol depending on performance level (advanced or highly advanced athletes) (p < .05). Regardless of the performance level, muscle damage and a reduction in performance could be induced by the training protocol. Only CBD oil was associated with a reduction in myoglobin concentration (p < .05) in advanced athletes. Concerning immune activity, a significant decrease in platelets lymphocyte ratios was observed in advanced athletes after placebo treatment (p < .05). CBD oil application showed a slight inhibitory effect (p < .10). Moreover, the reduction in performance differs between the performance levels. A significant decrease in CMJ was observed in advanced athletes and a decreasing trend in BS was observed in highly advanced athletes after placebo treatment (p < 0.10). Both CBD products do not affect performance parameters. For inflammatory parameters, no effects were observed.Conclusion It was found that the performance level of the subjects was a decisive factor and that they responded differently to the training protocol and the CBD application. However, no clear effects of either CBD product were found and further research is needed to identify the long-term effects of CBD application.